The contractionary effects of protectionist trade policy in a dollarized economy - Diego F. Grijalva; Carlos Uribe-Terán; Ivan Gache (Inter-American Development Bank (IDB), 2024)
This study analyzes the firm-level impacts of temporary safeguard import tariffs implemented in Ecuador from 2015 to 2017. Employing a difference-in-differences methodology, we explore the policy's effects on a unique dataset combining firm- and product-level data. We focus on the direct effects on importing firms and indirect effects through the value chain. The analysis shows, that while the safeguards significantly reduced imports, they also resulted in short-run negative scale effects on firms. These include reduced sales, employment, labor costs, and material costs, without positive impacts on local firms in import-competing industries. Overall, our findings suggest a contractionary effect of protectionist policies, particularly in a dollarized economy, highlighting the complex implications of trade measures on firm performance and economic sectors.
Keywords: F13; F14; F16; O24; O54; 330; Trade policy; Protectionism; Input-output linkages; Emerging markets; LatinAmerica